Obvladovanje kakovosti pri sanaciji armirano betonskih silosov za cement - Ipavec, Zdenko (Strojniški vestnik, 2000)
In this paper a sample of a quality management in the reconstruction of a reinforced concrete objects - specialy surfaces (walls) of silos for the cement powder warehousing is described. All project phases have been studied silos condition recording before reconstruction, reconstruction aim definition, reconstruction activity planning, reconstruction plan verification, executor selection, systematic reconstruction quality assurance by executor supervision of reconstruction quality by investor and verification by an external independent institution.
Keywords: obvladovanje kakovosti; beton armirani; saniranje objektov; silosi za cement; sanacija; silosi